2021
DOI: 10.3390/ijms221810058
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Alterations in a Transgenic Model of Tuberous Sclerosis Complex: Relevance to Autism Spectrum Disorders

Abstract: Tuberous sclerosis complex (TSC) is a rare, multi-system genetic disease with serious neurological and mental symptoms, including autism. Mutations in the TSC1/TSC2 genes lead to the overactivation of mTOR signalling, which is also linked to nonsyndromic autism. Our aim was to analyse synaptic pathology in a transgenic model of TSC: two-month-old male B6;129S4-Tsc2tm1Djk/J mice with Tsc2 haploinsufficiency. Significant brain-region-dependent alterations in the expression of several synaptic proteins were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
(103 reference statements)
3
5
0
Order By: Relevance
“…In turn, post-mortem histological examinations have revealed increased density of both the dendritic spines and excitatory synapses in the brains of ASD individuals [ 25 , 75 , 76 ]. In addition, our previous findings support and extend the evidence that links mTOR-hyperactivity with synaptic pathology both in Tsc2-haploinsufficient mice [ 77 ] and in environmental-triggered rat models of ASD [ 37 , 38 ]. Previously, we revealed that the inactivation of the Tsc2 gene triggers pathological alterations in both synaptic ultrastructure and in the expression of several key synaptic proteins [ 77 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In turn, post-mortem histological examinations have revealed increased density of both the dendritic spines and excitatory synapses in the brains of ASD individuals [ 25 , 75 , 76 ]. In addition, our previous findings support and extend the evidence that links mTOR-hyperactivity with synaptic pathology both in Tsc2-haploinsufficient mice [ 77 ] and in environmental-triggered rat models of ASD [ 37 , 38 ]. Previously, we revealed that the inactivation of the Tsc2 gene triggers pathological alterations in both synaptic ultrastructure and in the expression of several key synaptic proteins [ 77 ].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, our previous findings support and extend the evidence that links mTOR-hyperactivity with synaptic pathology both in Tsc2-haploinsufficient mice [ 77 ] and in environmental-triggered rat models of ASD [ 37 , 38 ]. Previously, we revealed that the inactivation of the Tsc2 gene triggers pathological alterations in both synaptic ultrastructure and in the expression of several key synaptic proteins [ 77 ]. However, the interaction between tubers, cognitive dysfunctions, and ASD in TSC individuals during development is still elusive and requires further investigation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Experimental (animal) models, especially based on rodents, are a valuable tool in translational neuroscience research [ 81 ], helping to target a wide range of brain disorders, including mTORopathies and epilepsy [ 82 ] (see Table 2 for details). For example, young adult male B6-129S4-Tsc2tm1Djk/J mice represent a useful transgenic model of TSC with Tsc2 haploinsufficiency and region-specific alterations in the expression of multiple synaptic proteins [ 83 ]. These mice display increased presynaptic VAMP1/2 and phospho-synapsin-1 (Ser62/67) immunoreactivity, along with serious ultrastructural anomalies (e.g., a fuzzy synaptic density structure, more synaptic vesicles, delaminated myelin and larger, heavier brain), elongated swollen synaptic mitochondria (markers of their degradation), distended Golgi apparatus and polyribosomes in the cytoplasm (indicative of aberrant protein metabolism) and altered behaviors (e.g., novel object recognition deficits) [ 83 ].…”
Section: Animal Models Of Mtoropahic Epilepsymentioning
confidence: 99%